Investigating EFL Teachers’ Perceptions and Meanings on Digital Storytelling in Language Learning: A Narrative Approach - Nirwanto Maruf; Kuchakovska Halyna (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2023)
The study was aimed at understanding the perceptions and meaning of EFL teachers when using digital storytelling for language learning in the classroom. Seven EFL teachers with experiences using digital storytelling in their language instruction were recruited for this study. Analysis of the data collected from the participants revealed several themes related to EFL teachers’ perceptions and meanings of using digital storytelling for language learning in the classroom. The results of the study indicate that teachers have hold overwhelmingly positive perceptions of digital storytelling as a teaching and learning tool in the classroom. Specifically, they view it as a highly creative and engaging teaching approach that allows students to express themselves in a more personalized and meaningful way. In addition, they believe that digital storytelling facilitates language acquisition and enhances cultural understanding. Furthermore, these findings are consistent with related theories in the field of language teaching and learning. However, the study also highlighted the challenges and limitation of using digital storytelling, such as resource constraints and technical difficulties. Therefore, educators should be mindful of these limitations and plan accordingly when incorporating digital storytelling into their language instruction.